A Meningkatkan Hasil Belajar Matematika Siswa Melalui Model Pembelajaran Teams Games Tournament (TGT) Pada Siswa Kelas VII: Meningkatkan Hasil Belajar Matematika Siswa Melalui Model Pembelajaran Teams Games Tournament (TGT) Pada Siswa Kelas VII - rati, Nursidrati (STKIP Al-Amin Dompu, 2024)
This research aims to improve the learning outcomes of class VII students at SMP Negeri 5 Woha in Mathematics subjects using the TGT type Cooperative Learning Model. This research is collaborative classroom action research. The subjects in this research were class VII students at SMP Negeri 5 Woha with a total of 18 students. This research took place in two cycles. Cycle 1 consists of 3 meetings and cycle 2 consists of 2 meetings. Data collection techniques in this research are observation and objective tests. The data analysis techniques used are quantitative descriptive and qualitative descriptive. The success indicator is determined if the class average increases from pre-action, cycle I and cycle II. The research results show that students' Mathematics learning outcomes have increased. This is shown by an increase in the class average value, namely at the time of pre-action it was 6.8, increasing to 7.5 in cycle I, then increasing again in cycle II to 8.05. Apart from that, from the observation data obtained before the action was given, students seemed less active in learning activities, learning activities were more dominated by the teacher. After being given action, students looked active both during question and answer activities and during group activities.